Evidence-based clinical practice guidelines for peptic ulcer disease 2026 - Mitsushige Sugimoto; Tomoari Kamada; Masanori Ito; Junichi Iwamoto; Tadayoshi Okimoto; Shoko Ono; Takeshi Kanno; Toshimi Chiba; Kengo Tokunaga; Sachiyo Nomura; Takahisa Murao; Toshio Watanabe; et al. (Journal of Gastroenterology, 2026)
Abstract In 2026, the fourth edition of the evidence-based clinical practice guidelines for peptic ulcer disease by the Japanese Society of Gastroenterology (JSGE) was revised. These revised guidelines cover epidemiology, hemorrhagic peptic ulcers, Helicobacter pylori eradication therapy, non-eradication therapy, drug-induced ulcers, non -H. pylori , and nonsteroidal anti-inflammatory drug (NSAID) ulcers, remnant gastric ulcers, surgical treatment, and conservative therapy for perforation and stenosis. Although H. pylori infection and NSAIDs use remain two major causes of peptic ulcers, the prevalence and mortality rates of peptic ulcer have been declining due to the widespread use of eradication therapy and development of potent acid-inhibitory drugs in recent years. However, an increasing trend in idiopathic ulcers and ulcers caused by non- H. pylori Helicobacter (NHPH) infection has attracted attention. In this revised edition, therapeutic algorithms for the treatment of peptic ulcers based on H. pylori infection, low-dose aspirin (LDA) or NSAID use, ulcer history, and ulcer complications (e.g., hemorrhage) remain largely unchanged. This edition shows options for H. pylori eradication in various situations compared with the previous edition, and recommends the most effective regimens, regardless of Japanese insurance coverage. In addition, a new flowchart outlining the eradication treatment process has been presented. Compared with the previous version, the main changes in pharmacological treatment have been made: due to its acid-inhibitory characteristics compared with proton pump inhibitors and increased evidence of its efficacy and safety, vonoprazan has now been selected as the first-line treatment for peptic ulcers and NSAID- and LDA-induced ulcers.